2018
DOI: 10.1145/3199524.3199534
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of WebRTC-based Video Conferencing

Abstract: WebRTC has quickly become popular as a video conferencing platform, partly due to the fact that many browsers support it. WebRTC utilizes the Google Congestion Control (GCC) algorithm to provide congestion control for realtime communications over UDP. The performance during a WebRTC call may be influenced by several factors, including the underlying WebRTC implementation, the device and network characteristics, and the network topology. In this paper, we perform a thorough performance evaluation of WebRTC both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 24 publications
1
29
0
4
Order By: Relevance
“…Moreover, the transmission rate of WebRTC is able to adapt to the available bandwidth of the network, whereas Skype platform adjusts the video resolution to adapt to the network condition [20,21,24]. Similar findings were observed by another study reported in [25], which indicated that the WebRTC-based video conference system could perform well on the network less than 1 Mbps of bandwidth capacity. These outcomes supported the results of this study.…”
Section: Discussionsupporting
confidence: 66%
“…Moreover, the transmission rate of WebRTC is able to adapt to the available bandwidth of the network, whereas Skype platform adjusts the video resolution to adapt to the network condition [20,21,24]. Similar findings were observed by another study reported in [25], which indicated that the WebRTC-based video conference system could perform well on the network less than 1 Mbps of bandwidth capacity. These outcomes supported the results of this study.…”
Section: Discussionsupporting
confidence: 66%
“…Focusing on the impact of network performance, Jansen et al [6] investigate the effects of latency, packet loss, and bandwidth on the performance of WebRTC-based videoconferencing in both synthetic and real wired and wireless environments. In particular, they focus on the impact of the Google Congestion Control (GCC) algorithm, utilized by WebRTC to provide congestion control for real-time communications over UDP.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Filtering noise without altering the speech quality is a huge challenge. It can be done by using software filters (e.g., WebRTC library [15][16][17]) and/or hardware filters [18]. However, incidental noise may require a sophisticated active noise reduction.…”
Section: Influence Of Dynamically Changing Environmentmentioning
confidence: 99%